Ficção Interativa: O potencial narrativo do Livro-Jogo em diferentes contextos literários - Sandrine Teixeira Malta (2018)
The learning of literary contents is considered by the Ministry of Education and Science, one of the great components in the discipline of the Portuguese Language. Despite the reformulations in the Curriculum Goals and the adjustment of the program, the students' difficulties in understanding texts continue to be visible. It is possible to verify that the interpretation of the student is conditioned, and can lead to serious gaps as an individual inserted in a society. Faced with such a reality, which has been pointed out and discussed by the teachers at the moment of evaluation, it is necessary that the students maintain an early contact with different vocabularies and new ways of exploring literary contents. To do this, activities to be carried out in classroom context, according to external factors of the school and with the help of the Teacher, are being presented as one of the ways to guarantee better results in the final moment of evaluation. Despite some considerable progress in overcoming learning-related difficulties, teaching has not yet emerged sufficiently from the benefits of new technologies. The appearance of interactive narratives and videogames, presented visible changes in the routine of the individual. The use of serious games, for example, has been recognized and adapted to encourage and encourage people to perform tasks. Bearing in mind the complexity of these new instruments, this work intends to find research lines for the creation of a tool capable of narrating and disrupting literary contents and, essentially, of motivating and supporting a preparation course for the national exam. Being evaluated and developed with a control group composed of students and teachers, usability tests and recurrent methodologies to User-Centered Design to correspond directly to the requirements of the target audience.